The Woman in White - Collins, Wilkie (New York Oxford University Press, 1993)
The Woman in White is Wilkie Collins' fifth published novel, written in 1859. It is considered to be among the first mystery novels and is widely regarded as one of the first in the genre of "sensation novels"
Include Illustrations
Keywords: Sshort Story